Can codes of conduct help rebuild trust in the UK Financial Services Industry? - Riley, Neil (2012)
This MBA project is a company hosted management project. This work has been commissioned by the Question of Trust Campaign. This recently-launched campaign aims to improve the levels of trust within the UK financial services industry. The campaign approach involves concern over ‘soft controls’ within the industry, related to ethics and values. The position of the campaign is that too much emphasis has been placed upon ‘hard controls’ such as regulation; ‘compliance’ is not necessarily the same as ‘doing the right thing’.